Canola Cost-Return Budget in South Central Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Shoup, Douglas; Holman, John (My University, 2015)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in south central Kansas.
MF2421_2015_04
Keywords: MF2421; Crops; Economics; MF